2016
DOI: 10.1007/s11109-016-9378-0
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy: Political Attitudes and Economic Behavior

Abstract: Please note that the Publication Information provides general citation information and may not be appropriate for your discipline. To receive help in creating a citation based on your discipline, please visit http://libguides.sjfc.edu/citations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Moreover, the "Michigan model" states that psychological attachment raises a perceptual screen such that individuals tend to see what is favorable to their political bias (Campbell 1960). In line with this thesis, other studies confirm that political beliefs affect everything from consumption and investment behavior (Key and Donovan 2017;Hong and Kostovetsky 2012;Kaustia and Torstila 2010) to how we selects our spouses (Iyengar et al 2018). These findings raise some doubts about treating humans as primarily economic voters (Evans and Andersen 2006;Ramirez and Erickson 2013).…”
Section: Previous Research and Hypothesessupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, the "Michigan model" states that psychological attachment raises a perceptual screen such that individuals tend to see what is favorable to their political bias (Campbell 1960). In line with this thesis, other studies confirm that political beliefs affect everything from consumption and investment behavior (Key and Donovan 2017;Hong and Kostovetsky 2012;Kaustia and Torstila 2010) to how we selects our spouses (Iyengar et al 2018). These findings raise some doubts about treating humans as primarily economic voters (Evans and Andersen 2006;Ramirez and Erickson 2013).…”
Section: Previous Research and Hypothesessupporting
confidence: 79%
“…A growing body of research argues that economic outcomes could themselves be functions of political beliefs. For instance, studies show that citizens engage in different types of consumption and investment patterns, or interpret changes in the economic context differently, depending on their political identity (Evans and Andersen 2006;Ramirez and Erickson 2013;Key and Donovan 2017;Hong and Kostovetsky 2012;Kaustia and Torstila 2010). While there is an emerging literature that attempts to circumvent these issues with quasi-experimental designs, such as analyzing large lottery winnings (Doherty et al 2006;Peterson 2016;Powdthavee and Andrew 2014), these types of wealth shocks are exceedingly rare and often disproportionally large, and therefore likely of little practical importance to policy.…”
Section: Introductionmentioning
confidence: 99%
“…After Democrats took control of both Houses of Congress, Democratic (Republican) respondents reported greater optimism (pessimism) about the economy as a whole and about their personal finances. This result indicated that partisanship and partisan control of government had some causal impact on economic views, though it is unclear precisely which mechanism mediates that effect ( compare Gerber & Huber, 2009, 2010; Key & Donovan 2016 with Anson, 2017; McGrath, 2017; Prior et al, 2015; Bullock et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…The proper implementation of CITES calls for parties to establish monitoring and enforcement capacity as well as prohibition and punishment measures [3], yet countries are frequently faced with changing political environments in striving to comply with supranational laws [12]. For instance, some interest groups can make compliance difficult in order to foster their own economic advantages [13], and some exemptions within the law can complicate enforcement [2]. At the global and national levels, sunshine and carrot and stick instruments are used to encourage compliance via making information widely available, even when limited [14] and using both positive and negative incentive structures [5].…”
Section: Introductionmentioning
confidence: 99%